Edupreneurship through Teaching Factory in the Light Vehicle Engineering Skills Program at Muhammadiyah Kutowinangun Vocational School - Tri Kuat; Rendra Ananta Prima Hardiyanta; Eko Pawitno; Muhammad Eko Agung Nugroho (Journal of Vocational Education Studies, 2023)
This research aims to (1) analyze the implementation of edupreneurship through a teaching factory in the light vehicle engineering skills program in Kutowinangun Muhammadiyah Vocational School; (2) analyze the driving factors for implementing edupreneurship through a teaching factory in the light vehicle engineering skills program at Muhammadiyah Kutowinangun Vocational School; and (3) analyzing the factors inhibiting the implementation of edupreneurship through a teaching factory in the light vehicle engineering skills program at Muhammadiyah Kutowinangun Vocational School. This qualitative research uses descriptive methods approach. Data collection was carried out by interviews, observations, and documentation. Research subjects are: principal, deputy principal curriculum fields, productive teachers, and students. The data analysis technique uses interactive analysis, starting from data collection and then reducing the data; after reduced, presented the data, and finally verified. The validity of the data was tested by triangulation. Findings in this research revealed that (1) Planning , organizing, implementing, and monitoring/evaluation, implementation of edupreneurship through the teaching factory , competency in light vehicle engineering skills at Muhammadiyah Kutowinangun Vocational School has gone very well in carrying out vehicle service and maintenance from inside and outside the school, the implementation of edupreneurship through the teaching factory makes a contribution to foster students' entrepreneurial spirit; (2) Factors driving the success of edupreneurship consist of: quality educational resources, adequate infrastructure both in quantity and quality, standard operational procedures according to industry standards, quality services, an established service marketing network, and students is to be directly involved in the work; (3) Inhibiting factors, namely the fluctuating number of customers, limited operational time, limited spare parts for all brands, and varying public perceptions of vocational school service results.